2013
DOI: 10.2478/amma-2013-0066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Skeletal Maturation Using Lower First Premolar Mineralisation

Abstract: Background: Dental age assessment is very useful in the pediatric dentist's and orthodontist's everyday practice. The eventual lack of correlation between dental age, skeletal maturation and chronological age can infl uence treatment procedures regarding mostly their application time. The aim of our study was to investigate the relationship between dental age based on the calcifi cation stages of the fi rst lower premolar (PM1i) and skeletal maturity stages using cervical vertebrae (C2, C3, C4) among Romanian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…According to this study, correlation of mandibular 1st premolar and skeletal age is higher than the mandibular 2nd molar. This is the similar findings of Rózylo-Kalinowska et al 21 Valizadeh et al 30 and Krisztina et al 31 study. 32 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to this study, correlation of mandibular 1st premolar and skeletal age is higher than the mandibular 2nd molar. This is the similar findings of Rózylo-Kalinowska et al 21 Valizadeh et al 30 and Krisztina et al 31 study. 32 …”
Section: Discussionsupporting
confidence: 90%
“…The mandibular premolar is also a precise indicator because the development of the mandibular 1st premolar begins at 21–24 months and ends at the age of 12–13 years. Rozylo-Kalinowska et al 21 reported that the calcification stages of mandibular premolars and canine shows the highest correlation with CVMI.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate mandibular growth potential left, the patient must be localized on is growth curve, and many biologic indicators have been proposed: increase in body height, menarche, breast and voice changes, dental development and eruption, middle phalanx maturation of the third finger, maturation of the hand and wrist, and cervical vertebral maturation [3,[5][6][7][8]].…”
Section: Importance Of the Work And Its Interest For Orthodontics Commentioning
confidence: 99%
“…To estimate mandibular growth potential, the patient must be localized on is growth curve, and many biologic indicators have been proposed; increase in body height, menarche, breast and voice changes, dental development and eruption, middle phalanx maturation of the third finger, maturation of the wrist and cervical vertebral maturation [ 5 , 6 , 7 , 8 ].…”
Section: Importance Of the Work And Its Interest For The Orthodontmentioning
confidence: 99%